Implementasi Teori Behavioristik dalam Meningkatkan Kemampuan Berbahasa Arab Siswa - `Alin Nur Salsabila; Hamdah Hanifah; M. Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to explore the application of behavioristic theory in education and identify its challenges and effectiveness in improving student learning outcomes. Behavioristic theory, which focuses on the relationship between stimulus and response, explains that individual behavior can be modified through positive and negative reinforcement. Using a qualitative method with a case study approach, data were collected through in-depth interviews and classroom observations. The results indicate that while this theory is effective in shaping desired behaviors, there are challenges related to neglecting internal factors such as students' emotions and motivation. This research recommends integrating positive aspects of behavioristic theory with a more holistic approach to meet students' emotional and social needs